THE IMPLEMENTATION OF PROBLEM BASED LEARNING ACTIVITY THROUGH ONLINE SCHOOL FIELD PRACTICE - Budiarti Putri Uleng; Nadya Nurhidayah Nurdin (Jurnal Ilmiah Global Education, 2023)
The application of problem-based learning is a style of methodology that puts the idea of learning from facts and looking at real-world problems into practice. In order to examine mediated communication, this study used a qualitative ex experimental design using qualitative techniques. This method, known as the "qualitative experiment," makes use of in-depth interviews and focus groups under randomized stimulus circumstances that are commonly found in experimental research. In this work, observational data collecting and document analysis were the primary methods of data acquisition. This study intends to examine how problem-based learning is used in online English learning activities. Highlights from the approach's implementation initiatives include: 1) The concept grasp of the student regarding the subject matter; and 2) the student's critical thinking. These findings suggest that the qualities of the Problem Based Learning approach, namely the student's independence and social competency, had emerged.